2020
DOI: 10.3390/nu12020298
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Extrinsic Wheat Fiber Supplementation on Fecal Weight; A Randomized Controlled Trial

Abstract: Higher fiber intake may confer beneficial effects on health. Our objective was to investigate the impact of 10 g extrinsic wheat fiber on fecal bulk. Therefore, we performed two randomized intervention studies in which we provided extrinsic wheat fiber-enriched products or appropriate control products for five days together with normal diet. In one trial, 10 participants received fiber-enriched food products, whereas in the second study, 19 participants supplemented their daily diet with fiber-enriched drinks.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 28 publications
1
15
0
Order By: Relevance
“…As for the individual SCFAs, a total of 26 studies showed no overall significant differences [9,10,12,14,[16][17][18][19][20][21][23][24][25]27,28,[32][33][34][35][36]38,39,43,[47][48][49]. Two studies [40,42] reported a significant increase in acetate, butyrate, and propionate, while another two reported a significant decrease for all three SCFAs [11,13].…”
Section: Analysis and Main Effects Of Treatments On Scfasmentioning
confidence: 99%
See 4 more Smart Citations
“…As for the individual SCFAs, a total of 26 studies showed no overall significant differences [9,10,12,14,[16][17][18][19][20][21][23][24][25]27,28,[32][33][34][35][36]38,39,43,[47][48][49]. Two studies [40,42] reported a significant increase in acetate, butyrate, and propionate, while another two reported a significant decrease for all three SCFAs [11,13].…”
Section: Analysis and Main Effects Of Treatments On Scfasmentioning
confidence: 99%
“…The main characteristics of the 42 included studies are reported in Table S1. A total of 44 trials were available for detailed analysis from the 42 included studies since two of the publications [9,10] reported two separate trials. Specifically, 10 out of the 44 trials were parallel randomized controlled trials (RCTs), while 34 were cross-over RCTs.…”
Section: Study Design and Interventions Testedmentioning
confidence: 99%
See 3 more Smart Citations